Interplay of Na+ Balance and Immunobiology of Dendritic Cells - Neubert, Patrick; Schröder, Agnes; Müller, Dominik N.; Jantsch, Jonathan (Frontiers in Immunology, 2019)
Local Na+ balance emerges as an important factor of tissue microenvironment. On the one hand, immune cells impact on local Na+ levels. On the other hand, Na+ availability is able to influence immune responses. In contrast to macrophages, our knowledge of dendritic cells (DCs) in this state of affair is rather limited. Current evidence suggests that the impact of increased Na+ on DCs is context dependent. Moreover, it is conceivable that DC immunobiology might also be influenced by Na+-rich-diet-induced changes of the gut microbiome.